KEKUATAN BISNIS “DEKKE NANIURA”, KEUNIKAN KULINER TRADISIONAL SUKU BATAK (TOBA) DI PROVINSI SUMATERA UTARA, PULAU SUMATERA, INDONESIA - Parlindungan Tambunan (Jurnal Hutan Tropis, 2021)
The diversity of the people of Indonesia gives a variety of different fields including ethnic, culture, ras, religion, and between groups. Each ethnic group in Indonesia differs in how to obtain knowledge, some are hereditary and there is a process of learning from others. One example, the Batak ethnic (Toba) in Sumatera Island has knowledge about flora. They use flora for food processing, medicine, and living equipment. From food processing, the Batak ethnic (Toba) have diverse knowledge of food processing (culinary). One of the famous traditional culinary of the Batak ethnic (Toba) in Sumatra Island is Dekke Naniura. Dekke Naniura is one of the culinary traditional of the Batak ethnic (Toba) in Sumatera Island. Dekke Naniura is unique, because Dekke Naniura is served from fresh raw goldfish which is given the simple spices (easily available) and the water of Unte Jungga fruit (Citrus hystrix DC.) So that goldfish are not fishy and goldfish meat becomes soft without any process cooking on fire, or after being inhabited for 3 to 5 hours Dekke Naniura is ready for consumption. The uniqueness and originality of the traditional culinary processing of the Batak ethnic (Toba) "Dekke Naniura" has added value that can be calculated to preserve the taste. Therefore, the preservation of the taste of Dekke Naniura must be maintained by a culinary management, which has a standard operating system for sure, namely from the selection of ingredients to how to eat. With a certain standard operating food, a unique traditional culinary business can be operated as a strategic and promising industrial business. The uniqueness of a traditional culinary is the power of business that can create and contribute to the economy in a sustainable way from generation to generation. Dekke Naniura is one of the advantages of origin or representing the symbol of the North Tapanuli region, the Batak ethnic (Toba) in Sumatera Island.